Norwegian Public Health Nursing Students' Experiences with the Transition from Classroom to Online Lectures: Benefits and Challenges - Bente Sparboe-Nilsen; Victoria Telle Hjellset; Milada Cvancarova Hagen; Lisbeth Valla (MDPI AG, 2024)
The integration of technology in higher education increased online courses available to students, although traditional face-to-face interaction remains dominant. The COVID-19 pandemic forced a rapid transition to emergency remote teaching (ERT), impacting public health nursing (PHN) education in Norway, which primarily consists of adult learners. The impact of the transition to online-only lectures on these students remains largely unexplored. The aim of this study is to examine how Norwegian PHN students experienced the transition from traditional classroom lectures to online-only lectures during the global pandemic. It also identifies the self-reported advantages and challenges associated with online-only lectures and whether this transition affected their perceived learning outcome. A cross-sectional sample of public health nursing (PHN) students (n = 275) participated in a survey in from May to November 2020. The questionnaire was specifically developed for this study and covers student motivation, perceived benefits and challenges of transitioning to online lectures, peer collaboration, and self-assessed learning outcomes. It was distributed to the PHN students via their respective education's LMS system. Most PHN students managed the technical aspects of the abrupt transition to online-only lectures effectively. They reported high digital competence, found the transition relatively easy, and remained motivated to continue their studies. Despite these positives, students reported a reduction in learning outcomes compared to classroom lectures. Challenges included the missing face-to-face interaction with peers, difficulties in managing childcare, and issues with structuring their studies.